Implementasi Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Daerah pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kota Surabaya - Yenny Rinfayanti; Rini Jefri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to find out whether the Surabaya City Regional Financial and Asset Management Agency uses the accounting information system for cash receipts and disbursements correctly and in accordance with regulations. This research uses documentation, interviews and literature study. Meanwhile, the data analysis technique used is qualitative descriptive analysis. This research begins with creating a list of interview questions, conducting interviews, matching documentation and observations, as well as creating analyzes and reports. The results of this research indicate that the Surabaya City BPKAD has implemented SIA in accordance with government regulations regarding accountable financial transparency. This financial application regulates financial administration, including receipts, expenditures, accounting records and all accountability reports. The obstacle faced is that there are too many applications applied so that miscalculations often occur between applications. All stages of receipt, expenditure and bookkeeping have been implemented in an application system and follow applicable laws.